A Flexible Cystoscope Based on Hydrodynamic Cavitation for Tumor Tissue Ablation - Abbasiasl, Taher; Sutova, Hande; Niazi, Soroush; Celebi, Gizem; Karavelioglu, Zeynep; Kirabali, Ufuk; Yilmaz, Abdurrahim; Uvet, Huseyin; Kutlu, Ozlem; Ekici, Sinan; Ghorbani, Morteza; Kosar, Ali (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
Objective: Hydrodynamic cavitation is characterized by the formation of bubbles inside a flow due to local reduction of pressure below the saturation vapor pressure. The resulting growth and violent collapse of bubbles lead to a huge amount of released energy. This energy can be implemented in different fields such as heat transfer enhancement, wastewater treatment and chemical reactions. In this study, a cystoscope based on small scale hydrodynamic cavitation was designed and fabricated to exploit the destructive energy of cavitation bubbles for treatment of tumor tissues. The developed device is equipped with a control system, which regulates the movement of the cystoscope in different directions. According to our experiments, the fabricated cystoscope was able to locate the target and expose cavitating flow to the target continuously and accurately. The designed cavitation probe embedded into the cystoscope caused a significant damage to prostate cancer and bladder cancer tissues within less than 15 minutes. The results of our experiments showed that the cavitation probe could be easily coupled with endoscopic devices because of its small diameter. We successfully integrated a biomedical camera, a suction tube, tendon cables, and the cavitation probe into a 6.7 mm diameter cystoscope, which could be controlled smoothly and accurately via a control system. The developed device is considered as a mechanical ablation therapy, can be a solid alternative for minimally invasive tissue ablation methods such as radiofrequency (RF) and laser ablation, and could have lower side effects compared to ultrasound therapy and cryoablation.
Keywords: Hydrodynamics; Tumors; Probes; Acoustics; Ultrasonic imaging; Radio frequency; Liquids; Hydrodynamic cavitation; cystoscope; tumor ablation; cavitation treatment; ATOMIC-FORCE; FOCUSED ULTRASOUND; BUBBLE DYNAMICS; HISTOTRIPSY; SURGERY; ORIFICE; Engineering